2014
DOI: 10.1530/erc-14-0239
|View full text |Cite
|
Sign up to set email alerts
|

The role of corticotropin-releasing hormone receptor 1 in the development of colitis-associated cancer in mouse model

Abstract: Patients with ulcerative colitis are at a very high risk of developing colorectal cancer. Corticotrophin-releasing hormone (CRH) family peptides and their receptors (CRHRs) are found to modulate inflammation and tumor cell growth. However, the role of CRH family peptides and their receptors in the inflammation-related colon cancer is still unknown. The aim of this study was to investigate the functions of CRHR1 signaling on the development of colitis-associated cancer (CAC). Crhr1-deficient (Crhr1 K/K ) mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…Chatzaki, et al have reported that CRHR2 expression in the colonic epithelial cells was down-regulated both in patients with moderately active UC and those in remission (37). CRHR1 has a pro-inflammatory and therefore a pro-tumorigenesis effect in terms of colitis associated cancer (38). Inhibition of the expression of CRHR2 correlates with tumor expansion, epithelial-mesenchymal transition, distant metastasis risk and poor survival in experimental CRC models and in CRC patients (39).…”
Section: Discussionmentioning
confidence: 99%
“…Chatzaki, et al have reported that CRHR2 expression in the colonic epithelial cells was down-regulated both in patients with moderately active UC and those in remission (37). CRHR1 has a pro-inflammatory and therefore a pro-tumorigenesis effect in terms of colitis associated cancer (38). Inhibition of the expression of CRHR2 correlates with tumor expansion, epithelial-mesenchymal transition, distant metastasis risk and poor survival in experimental CRC models and in CRC patients (39).…”
Section: Discussionmentioning
confidence: 99%
“…The corticotropin‐releasing hormone (CRH) system was initially identified as a hypothalamus‐directed mediator of neuroendocrine stress response, while recent studies suggest a link between CRH and the development of solid cancers . Preclinical studies showed the proinflammatory and procarcinogenic nature of CRH family peptides and their receptors, and the fact that they modulate immunity, inflammation and tumour cell growth .…”
Section: Discussionmentioning
confidence: 99%
“…; Liu et al. ). To date, few studies have defined the role of CRH in the regulation of pulmonary cellular immune and inflammatory responses (O'Kane et al.…”
Section: Discussionmentioning
confidence: 98%
“…Its ability to influence immune function is commonly associated with the release of adrenal corticotropic hormone (ACTH) from the adrenal glands, resulting in cortisol release that in turn translates into nonspecific immune suppression (Rodgers and Klugman 2011). Alternatively, CRH is also secreted in peripheral tissues (e.g., synovial tissue, gastrointestinal tract, placenta), where it is believed to modulate cellular immune and inflammatory responses through preferences in CRH receptors 1 and 2 activity (Peracoli et al 2011;Zhu et al 2011;Liu et al 2014). To date, few studies have defined the role of CRH in the regulation of pulmonary cellular immune and inflammatory responses (O'Kane et al 2006).…”
Section: Discussionmentioning
confidence: 99%